Effect of the use of organic manure with biochar on the morphological characteristics of Theobroma cacao pods CCN51 (2022)
The loss of soil fertility and pathogens directly affect cocoa yields. An alternative to these problems is the use of organic manures such as biochar (BC). The aim of this research was to measure the effects of various doses of cocoa BC (BCC) and banana BC (BCB) mixed with earthworm humus on the morphological parameters of cocoa pods CCN51. Four plots were delimited, in each one 15 plants per treatment were evaluated, which consisted of doses of 50 g (T1) and 75 g (T2) of BCC+humus, 50 g (T3) and 75 g (T4) of BCB+humus and 150 g of humus (T0-control plot). The highest averages of harvested cocoa pods (HC) corresponded to T0 (13.45 DM), followed by T3, T2, and T4, with no significant differences (p≤0.05) between treatments, but with the control plot. In diseased cocoa pods (DC) the highest value was 3.23 (T0) and the lowest average was 1.96. The percentage of healthy ears harvested ranged from 78.54% (T0) to 82.95 % (T4), with no significant differences. No significant differences were also obtained in ear length, ear diameter, and ear weight parameters. The range of 100 dry seed weight was 166.65 g (T0) to 185.56 g (T1) with significant differences among the treatments. The BC+humus treatments showed higher HC and lower DC values than those obtained in other investigations.